Action research through lesson study for the reconstruction of teachers' practical knowledge. A review of research at Málaga University (Spain). Issue 4 (8th August 2019) - Soto Gómez, Encarnación; Serván Núñez, María José; Trapero, Noemí Peña; Pérez Gómez, Ángel Ignacio
ABSTRACT: This article aims to set out our discussions, reflections and research at Málaga University (Spain) in relation to Lesson Study (LS), as a cooperative action research process. The paper aims to summarise the main findings of ten years of research, addressing the concepts and dilemmas found both in forming teachers' practical thinking and in the complex processes of reconstruction through LS. The results of our research provide evidence that it is a useful way to deal with the reconstruction of teachers' practical knowledge in teacher training. Teachers' practical knowledge should be more broadly seen as an active combination of theoretical knowledge, procedural knowledge and skills, attitudes, emotions, believes, and values: i.e. teachers' practical thinking. Most of these personal and professional resources are unconscious, or rather sub-conscious. Changes in teachers' practical thinking require more practical experience and reflexion: a dialectical process based around two key components: theorisation of practice and experimentation of reconstructed theory. The results of our research show that these dialectical process could be developed with LS as a particular way of developing AR, adding a complex, systematic, flexible and cooperative way of dealing with specific and contextual curricular innovation projects. We therefore conclude that LS could be a very useful path to follow in reconstructing teachers' practical thinking from within, strengthening the professional teaching community.